Outrage: Art, Controversy, and Society
XVI, 331 p.
Keywords: A study of controversy in the arts, and the extent to which such controversies are socially rather than just aesthetically conditioned. The collection pays special attention to the vested interests and the social dynamics involved, including class, religion, culture, and - above all - power.